AHSS auto stamping challenges: Rectifying springback - Mohtar, Shahimi; Baluch, Nazim Hussain; Abdullah, Che Sobry (Penerbit UTM Press, 2015)
To improve crash worthiness and fuel economy, the automotive industry is, increasingly, using Advanced High Strength Steel (AHSS).The main reason to utilize AHSS is their better performance in crash energy management, which allows one to down gauge with AHSS.In addition, these engineered AHSS address the automotive industry’s need for steels with higher strength and enhanced flammability.The improved capabilities the AHSS bring to the automotive industry do not bring new forming problems but certainly accentuate problems already existing with the application of any higher strength steel.These concerns include higher loads on presses and tools, greater energy requirements, and increased need for springback compensation and control.Springback problem, consistently, is one of the leading roadblocks hindering auto stamping productivity. This paper describes the origins and types of springback, characterizes what causes it, and elaborates ways to rectify it through, stabilization, compensation, and verification.